2023
DOI: 10.3389/fmed.2023.1289026
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between risk of developing bronchial asthma and frailty: a bidirectional two-sample Mendelian randomization study

Xiao Ma,
Haoran Xu,
Jinghui Xie
et al.

Abstract: BackgroundA potential link between asthma and frailty has been suggested in previous studies. However, the nature of the causal relationship between these two conditions warrants further investigation. Therefore, this study assessed the bidirectional causality between asthma and frailty risk using two-sample Mendelian randomization (MR).MethodsThe study data were obtained from the genome-wide association study (GWAS) dataset, with 337,159 samples representing asthma data and 175,226 samples representing frailt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Since two-way MR analysis was performed between each cytokine and OLP in this study, we used Bonferroni Hochberg correction, i.e., when p<0.00038 (0.05/ 132), it suggested that the analysis results were significant. However, because multiple analyses lead to very small p-values after correction, some results that might otherwise be associated are often overlooked, which we call suggestive association results, also known as potential positive results, i.e., results that were significant before Bonferroni correction (p<0.05) but not after correction (p>0.00038), and these results were also included in our analyses (39)(40)(41).…”
Section: Mr Analysismentioning
confidence: 99%
“…Since two-way MR analysis was performed between each cytokine and OLP in this study, we used Bonferroni Hochberg correction, i.e., when p<0.00038 (0.05/ 132), it suggested that the analysis results were significant. However, because multiple analyses lead to very small p-values after correction, some results that might otherwise be associated are often overlooked, which we call suggestive association results, also known as potential positive results, i.e., results that were significant before Bonferroni correction (p<0.05) but not after correction (p>0.00038), and these results were also included in our analyses (39)(40)(41).…”
Section: Mr Analysismentioning
confidence: 99%